The tumour immune landscape and its implications in cutaneous melanoma. (1st October 2020) - Attrill, Grace H.; Ferguson, Peter M.; Palendira, Umaimainthan; Long, Georgina V.; Wilmott, James S.; Scolyer, Richard A.
Abstract: The field of tumour immunology has rapidly advanced in the last decade, leading to the advent of effective immunotherapies for patients with advanced cancers. This highlights the critical role of the immune system in determining tumour development and outcome. The tumour immune microenvironment (TIME) is highly heterogeneous, and the interactions between tumours and the immune system are vastly complex. Studying immune cell function in the TIME will provide an improved understanding of the mechanisms underpinning these interactions. This review examines the role of immune cell populations in the TIME based on their phenotype, function and localisation, as well as contextualising their position in the dynamic relationship between tumours and the immune system. We discuss the function of immune cell populations, examine their impact on patient outcome and highlight gaps in current understanding of their roles in the TIME, both in cancers in general and specifically in melanoma. Studying the TIME by evaluating both pro‐tumour and anti‐tumour effects may elucidate the conditions which lead to tumour growth and metastasis or immune‐mediated tumour regression. Moreover, an in‐depth understanding of these conditions could contribute to improved prognostication, more effective use of current immunotherapies and guide the development of novel treatment strategies and therapies.